IT-Based Learning Media Training for Islamic Religious Education Teachers in Karawang Regency, Indonesia - Masruroh, Siti; Zainuri, Rahma Dilla; Rahmatiani, Lusiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2025)
This community service activity aimed to enhance the competence of Islamic Religious Education (PAI) teachers in Karawang Regency in utilizing information and communication technology (ICT) for learning. The training, conducted by the Faculty of Teacher Training and Education, Universitas Buana Perjuangan Karawang, focused on developing IT-based learning media that are interactive, innovative, and aligned with the needs of 21st-century education. A total of 80 teachers participated in the one-day workshop, which included lectures, practical sessions, and collaborative workshops. The results demonstrated significant improvement in teachers’ digital literacy, motivation, and ability to design interactive learning media, leading to enhanced teaching quality in PAI classes.